Art and the Irish Free State - visualizing nationhood (1922 - 1934) - SHORTALL, WILLIAM MARY (Trinity College Dublin. School of Histories & Humanities. Discipline of History Of Art, 2020)
This thesis examines how the Irish Free State harnessed visual art for its political purposes in the 1922-34 period. The time frame chosen for this study is purposeful. It spans two different Post-Treaty government administrations and it demonstrates that during this period there were a variety of state sponsored art exhibitions held in Europe, America, and in Ireland Using a case study methodology, this research focuses on a number of national and international events in which the nascent State participated. It employs a political lens to explore how the State used art exhibitions and commissions associated with these events to serve different Irish governmental political agendas nationally and internationally. In doing so, it situates Irish visual art within the broader political, social, cultural and economic context of the early development of the Irish Free State. Events examined include the World Congress of the Irish Race held in Paris in 1922, various national Aonach Tailteanns, Dublin Civic Weeks over the period selected, the 1933 Chicago World's Fair, and participation in the British Empire Marketing Board scheme, the Eucharistic Congress and other endeavours. Looking to previously unused primary sources, this research determines that in this period the State was culturally aware and that administrations were actively engaging with the visual art community to serve its political needs. It shows that the State deployed art to consolidate its sovereignty, to assist its nation building program, to reconcile a people divided by the Civil War, to assert its definition of national identity, and to promote a positive international image of the country. Anxieties over the burgeoning State taking its place in the world - resulting in tensions between essentialist and epochalist stances as the government both looked to the past to assert its identity whilst being intent on modernising the State - are reflected, and to some extent resolved, in these events and art exhibitions. This research also contends that an Irish School of Art was recognised at the time - based on place and an aesthetic language - and it challenges the trope that the thatched cottage was an uncontested official icon of Irish art during this period. Furthermore, a number of neglected Irish Free State government supported art exhibitions and commissions are recovered and re-interpreted.
APPROVED
Keywords: Irish art politics history diplomacy exhibitions commissions